RADIOGRAPHIC AND ENDOSCOPIC EVALUATION OF ALIMENTARY TRACT FOREIGN BODIES AND THEIR SURGICAL CORRECTIONS IN SMALL ANIMALS - DILIPKUMAR, D; AMEERJAN , K; DHAGE , G P (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Twelve cases of alimentary tract obstructions were diagnosed either by survey radiography or endoscopy in small animals. Different surgeries viz., cervical oesophagotomy, thoracic oesophagotomy, gastrotomy and enterotomy were performed. Out of the 12 animals ten recovered uneventfully.Whereas, two animals died which were subjected to thoracotomy due to oesophageal leakage and pleurisy . Different foreign bodies causing alimentary tract obstructions were bone pieces, stones, nipple of feeding bottle, sewing needle, safety pin and cork of a bottle.
Keywords: Foreign body; Alimentary tract; Endoscopy; Radiography